A Concepts of Factor Land Value on Ahmad Yani Frontage Road, Surabaya. (July 2020) - Tampubolon, Y, K.; Utomo, C.
Abstract: The Surabaya City has a rapid infrastructure development as proven by the increasing value of land. One of the infrastructure developments is the construction of Ahmad Yani's Frontage Road. The value of land in Frontage Ahmad Yani continues to increase due to various factors. The purpose of this study analyzes what variables affect land value by using a descriptive analysis method based on journals and previous research. The results of this study uncovered four dominant variables that influence land values, namely location, land characteristics, externalities, and accessibility.